Physical Complaints of Pain and Heartburn as Part of The Symptoms of Somatization - Prasetya, Era Catur; Intan Afifah; Muhammad Hanun Mahyuddin; Ulaa Haniifah; Khadijah Hasanah Abang Abdullah (Jurnal Psikiatri Surabaya, 2023)
Introductions: One of the mental health disorders that have an impact on physical health is called somatization disorder. Somatization is characterized by the appearance of complaints of pain in body parts that occur repeatedly. Anxiety, various physical complaints, and an increasing number of symptoms accompany symptoms of somatization disorder. The most common physical complaint is heartburn. Case: This case report discusses the case of a 36-year-old woman who complained of heartburn by visiting various doctors, but no medical results showed any abnormalities. Purpose: This case report aims to provide a literature review of heartburn symptoms due to somatization. Discussion: The Relationship between Heartburn Levels and Somatoform Disorders Psychosocial stressors are related to psychological factors that influence medical conditions that cause prominent psychological and somatic disorders. Psychological disorders and vice versa can cause physical disturbances. The patient's bodily medical condition can cause psychological disorders. Patients with severe acute pain will experience anxiety, fear, and sleep disturbances. This is due to the patient's discomfort with his condition, where he suffers from the pain he experiences and cannot move. With increasing duration and intensity of pain, the patient may experience a depressive disorder, and then the patient will be frustrated and irritable towards those around him and himself. Conclusion: The high pain intensity in the patient will cause sensitivity and increase his concern for his physical, lowering the threshold for detecting physical sensations or expressing distress and pain.